Social media evaluation metrics - Ronalds Skulme; Valerijs Praude (Institute of Economic Research (IER), 2015)
Background. There are many methods how specialists can evaluate return of online marketing activities. Most of the methods out there are designed for versatile use. But each online marketing tool has its own unique specific metrics that should be taken into account when measuring the return of marketing activities. Authors believe that the methods that are designed to evaluate online marketing activities should also be more specific. Hence authors believe that more specific online marketing revenue determination methods should be proposed. Objectives. The aim of this paper is to propose a formula that can be used to evaluate the return of social media activities depending on consumer purchase decision process stage the online marketing activity was meant to influence. Methodology. To achieve the aim of this paper, following research methods were used: theoretical literature analysis, expert surveys, grouping and statistical analysis methods. Data. The proposed formula was based on the data that was collected from theoretical literature analysis and expert surveys. Results. The main result of this paper was to propose a formula, which can determine the return of social media activities based on purchase decision process stage the social media activity was meant to influence. Main contribution of the paper. This paper offers a new approach how to evaluate return of social media activities depending on which purchase decision process stage online marketing activity was meant to influence. This paper can be used as a basis for further researches where social media activity revenue evaluation methods are discussed. Marketing specialists can use this paper as an example how to evaluate return of social media activities.
Keywords: M31; 330; social media marketing; social media metrics; social media evaluation; consumer purchase decision process